Pengaruh Beban Kerja Terhadap Kinerja Karyawan Di PT Trans Musi Palembang Jaya - Rika Damaiyanti; Riri Hanifa (JURNAL EKOBIS Kajian Ekonomi dan Bisnis, 2021)
This study aims to determine how the form of workload is given, to determine employee performance and to find out how the effect of workload on employee performance at PT. Trans Musi Palembang Jaya. The sample in this study used a saturated sample with quantitative techniques so that in this study the entire population was sampled as many as 30 employees. The method used in this study is a sampling technique if all members of the population are used as samples because the population is relatively small. The results of hypothesis testing have proven that there is an influence between workload on employee performance, through the results of calculations that have been carried out, the tcount value of 6.772 with a significant level of result of 0.000 is smaller than 0.05, which means that the hypothesis in this study accepts Ha and rejects Ho. Statistical testing proves that workload has a positive effect on employee performance, meaning that there is an influence between workload variables on employee performance at PT. Trans Musi Palembang Jaya.